Strategi Pemasaran Kopi Bubuk Lumbung Mas Kelurahan Beng Kecamatan Gianyar Kabupaten Gianyar - MARYANA, I KADEK; USTRIYANA, NYOMAN GEDE; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Marketing Strategy of Lumbung Mas Coffee Powder Beng Village Gianyar District Gianyar Regency                This research is purpose to identify the key internal and external factors that influence the marketing of Lumbung Mas coffee powder and simultaneously formulating alternative strategies that can be selected by the company. This study uses IFAS matrix, EFAS matrix, IE matrix, and SWOT matrix to formulate alternative strategies . The results showed that internal environmental factors that influence is a good quality of coffee powder, product prices cheaper than competitor's product, the company is still conducting independently with simple equipment, as well as a limited amount of capital company. While external environmental factors that affect the availability of sufficient raw materials, demand for the consumption of beverages like coffee, competition with similar companies, as well as the increasing number of product substitution. Alternative strategies that need to be done by the company is developing a marketing network, improve customer service quality, strengthen cooperation with government agencies, improving the quality of human resources through training, improving the promotion and advertising, set prices to face the competition, improve the use of technology, as well as suppress any the possibility of leakage of operating costs.   Keywords: coffee, marketing strategy, Lumbung Mas